Apakah Belanja Pegawai, Belanja Barang dan Jasa, dan Belanja Modal berpengaruh Pada Pertumbuhan Ekonomi? - Mawaddah, Nadiyah; Lubis, Putri Kemala; Fadli, Rizky; Adriansyah, Teguh; Ramadhan, Wahyu (Asosiasi Dosen Akuntansi Indonesia, 2023)
Case Study: North Sumatra GRDP (2008-2022). Purpose of the study isto show the impact of labor costs, goods and services costs, and capital costs on the GDP growth rate of North Sumatra province in 2008-2022. The variables used in this study are gross domestic product (GDP) as the dependent variable and labor costs, expenditure on goods and services and capital expenditure as independent variables. The data used in this study are secondary data obtained from the official websites of DPJK and North Sumatra Bureau of Statistics (BPS). The analysis technique used in this study is a multiple regression analysis model processed with evews version 9. Based on the obtained evaluation results, personnel costs, goods, services and capital investments affect the gross national product of North Sumatra.